THE EFFECTIVENESS OF TEACHER-THEMED MOVIES TOWARDS PRE-SERVICE TEACHERS’ SELF-EFFICACY - Abdul Halim; Sunarti; Rani Herning Puspita; Azhar Aziz Lubis (Getsempena English Education Journal, 2019)
The aim of this study was to investigate the effectiveness of teacher-themed movie to elevate the pre-service teachers’ efficacy in coping with the real teaching field. Based on a pilot study conducted by the researcher in a public university in Kalimantan, Indonesia, many students of teacher training and education faculty did not choose their department solemnly. As a result, these pre-service teachers, when got involved in teaching practice at a school, did not believe they could handle real class situation. They believed that it was difficult to teach the students in their real field, especially when those students came with various personalities. Hence, an effort should be done to help the pre-service teachers develop their self-confidence to conduct actual classroom activities. The design of the study was experimental design with one group pre-test and post-test. The subjects of the research were 34 senior students of English Department. In collecting the data, questionnaires of self-efficacy were utilized. The data was analyzed by using SPPS program. The results showed the pre-service teachers, who watched an inspiring educational movie, where in the movie the teacher was able to handle some most difficult students and turned the students become ones with better personalities, could affect positively to their efficacy. In addition, the effect of watching such ennobling movie was significant to raise the pre-service teachers’ self-efficacy.